BACTERIOLOGICAL PROFILE AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN IN INTENSIVE CARE UNIT OF TERTIARY CARE HOSPITAL, AURANGABAD. - Patil, Praful S.; Ashok, Rangaiahagari (International Journal of Clinical and Biomedical Research, 2017)
Introduction: Multidrug resistant nosocomial infections are one of the leading causes of morbidity and mortality in hospitalized patients especially the critically ill patients in the intensive care unit (ICU), where a large number of drugs are administered to the patient which in turn leads to the generation of antibiotic resistant pathogens. Method: Over a period 12 months clinical samples (blood, urine, pus/ wound swabs, respiratory secretions etc) from patient admitted in ICU were processed according to the standard microbiologic methods, and their antimicrobial testing was performed using disk diffusion method. Results: A total of 464 samples, 164 (35.34%) were culture positive in which 133 (81.1%) samples were monomicrobial and 31(63) (18.9%) samples were polymicrobial. Out of 196 isolates were obtained, 127 isolates were Gram negative and 69 isolates were Gram positive organisms. The most common isolate was S. aureus (29.1%) and Klebsiella spp (26%) followed by E.coli (17.3%), Pseudomonas spp (13.8%), Streptococcus spp (5.1%), Acinetobacter spp (4.1%), Citrobacter (2.6%), Proteus Spp (1%) and Coagulase NegativeÂ StaphylococcusÂ (1%). Vancomycin and linazolid is more effect against the Gram positive organisms. For Gram negative organism’s carbapenems remain the drug of choice followed by amikacin. Conclusion: Institutional antimicrobial surveillance and proper infection control practices are essential to prevent and control multi drug resistant bugs in ICUs and hospital. KEY WORDS: Bacteriological profile; Antimicrobial profile; Intensive Care Unit infections; Nosocomial Infections.